Faith and spirituality in masters of world cinema - Morefield, Kenneth R. (Kenneth Robert), 1966- (Cambridge Scholars, 2008)
""Faith and Spirituality in Masters of World Cinema"" is a fascinating introduction to spiritual aspects in the works of some of the greatest filmmakers in the world, like Bergman, Dreyer and Tarkovsky, Avant Garde director Pedro Costa and Hollywood's golden boy Guillermo del Toro. It covers directors from around the world and shows diverse manifestations of spirituality in film; everything from how camera movements can imply spirituality to specific religions, like Islam and Christianity. ""Fai ...